Terminologi Perasaan dalam Antologi Puisi Sebelas Hari Istimewa Karya Ratna Ayu Budhiarti: Terminology of Feelings in the Anthology of ‘Sebelas Hari Istimewa’ Poetry by Ratna Ayu Budhiarti - Annisa, Andini Nur; Huri, Daman; Nurhasanah, Een (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to (1) describe the poetry structure contained in the poetry anthology Sebelas Hari Istimewa by Ratna Ayu Budhiarti, (2) find out the terminology of feelings contained in the poetry anthology Sebelas Hari Istimewa by Ratna Ayu Budhiarti. This research uses a qualitative approach with descriptive research methods. The theory used in this research is Herman Waluyo's poetry structure theory. There is also a supporting theory used, namely the theory of feeling Terminology from Sumandi Suryabrata. Sumandi explains that feelings are classified into indriyah and spiritual feelings. The subject of this research is the terminology of feelings and the object of this research is the poetry anthology Sebelas Hari Istimewa by Ratna Ayu Budhiarti. The results of this study are (1) analysis of the complete poetry structure, consisting of physical structure which includes: diction, concrete words, imagery, majas, versification, and typography and inner which includes: theme, taste, tone, and mandate; (2) analysis of feeling terminology in poetry which includes (a) indriyah feeling terminology including: sensory feelings, instincts, and responses; (b) spiritual feeling terminology including: divine, intellectual, beauty, and social feelings.